KEDOKTERAN EMERGENSI TANTANGAN, HARAPAN, DAN MASA DEPAN - Dradjat, Respati Suryanto (Jurnal Kedokteran Brawijaya, 2004)
The progress of science and technology in globalization era, forcing us to make-up the quality of education and services in the fild of Emergency Medicine (EM). As one of the teaching hospital in Indonesia, Saiful Anwar Hospital – Brawijaya University have developed this education programe. Various challenge, and opportunity have and will be faced to reach the futureof Indonesian Medical services to be able to compete in the era of global standardKey words:emergency, education, services